Penggunaan Media TikTok Pada Keterampilan Menulis Teks Prosedur Siswa Kelas VII SMP Negeri 7 Purwokerto - Nur Dian Khasanah, Siti; Nurlina, Laily (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This research aims to examine and describe the use of TikTok as a learning media and to depict the learning outcomes of students using TikTok in procedural text writing skills for seventh-grade students at SMP Negeri 7 Purwokerto. The method employed in this research is qualitative descriptive. Data in this study were collected using a triangulation technique (combination) involving observation, interviews, and document analysis. The findings of this research indicate that utilizing TikTok videos, specifically @resep_debm, for learning procedural text writing yields positive results. The average score for procedural text writing tests is 82.91, falling into the 'good' category. Seventeen students achieved an 'excellent' rating with scores ranging from 86 to 100, 15 were categorized as 'good' with scores ranging from 75 to 85, and four fell into the 'sufficient' category with scores ranging from 56 to 74. Based on these results, it can be concluded that the use of TikTok media in teaching procedural text writing can be effectively utilized by seventh-grade students at SMP Negeri 7 Purwokerto.